Effect of Age on Mechanical Properties of Human Tooth Enamel - Jing, Xia; Zhipeng, Yang; Kaiyong, Liu; Junjie, Lu; Xinyuan, He; Juan, Zhang; Yujie, Fan (Frontiers in Materials, 2022)
Dental health is closely related with people’s quality of life. Teeth are subject to different problems and risks over time. Therefore, studying the influence of age on mechanical properties of tooth enamel is of considerable importance. In this study, the collected human teeth were divided into four groups: deciduous (aged 6–12 years), juvenile permanent (aged 14–20 years), young adult permanent (aged 25–45 years), and older adult permanent (aged over 60 years) teeth. The mechanical properties of tooth enamel of all age groups were evaluated using a microhardness tester and laser confocal microscope. The results revealed that hardness of the deciduous teeth was much lower than that of permanent teeth. Hardness of young adult permanent teeth was the highest, followed by that of the older adult and juvenile permanent teeth. Deciduous teeth enamel had the highest fracture toughness, followed by that of young adult, juvenile, and older adult permanent teeth. The different chemical compositions and microstructures of enamel at different age groups resulted in the significant differences in mechanical properties. This research accords with the strategic requirement of improving peoples’ dental health, and its results are noteworthy in developing specific protocols for dental hygiene and clinical prevention.